Exploring the “Situation” of Situational Willingness to Communicate: A Volunteer Youth Exchange Perspective - Mady, Callie; Arnott, Stephanie (Canadian Journal of Applied Linguistics, 2010)
This paper presents the perspectives of youth participating in the Society for Educational Visits and Exchanges in Canada's Volunteer Youth Experience (VYE) as gathered by way of pre- and post-program questionnaires, observations, interviews, and journals. The pan-Canadian questionnaire results suggest that this short, bilingual volunteer experience enhances participant motivation to learn a second official language and to be part of the target community. Triangulated findings from observations, interviews and journals indicate that participants' willingness to communicate (WTC) in the second language (MacIntyre, Dörnyei, Clément, & Noels, 1998) may have been influenced by situational factors inherent to the volunteer experience such as access to native speakers of the target language and opportunities for authentic community participation.